The influence of principal's service quality and teachers' self-concept on emotional regulation in preschool teachers - Abu Hasan Agus; Baharun, Hasan; Rahmatillah, Alda Novita; Andayani, Sri Astutik (Jurnal Pendidikan Anak, 2025)
This study aims to analyze the influence of the quality of service of school principals and self-concept on the emotional regulation of preschool teachers. The research method uses a quantitative approach with a relational survey model. The research instruments included ServQual, Social Cognitive Theory, and Emotion Regulation Theory, with data from 100 teachers analyzed using SmartPLS. The results showed that the quality of the principal's services (tangibles, responsiveness, assurance, empathy) and teachers' self-concept (physical, social, academic, spiritual aspects) had a significant effect on the regulation of emotions (t-statistic > 1.96; p < 0.06). An R-square value of 0.736 indicates that the independent variable explains 73.6% of the variance in emotion regulation. The validity and reliability test showed that all indicators met the criteria (>0.5). These findings underscore the importance of principal leadership and positive self-concept in supporting teachers' emotional stability. This study provides strategic recommendations for education managers to improve teachers' professionalism and emotional well-being.